PENGARUH INTERVENSI GERAKAN LITERASI PRA-PEMBELAJARAN TERHADAP KETERAMPILAN MEMBACA SISWA KELAS V SDN MENANGGAL 601 SURABAYA - Sovia Putri Salsabilla; Rudy Sumiharsono; Danang Prastyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Pre-Learning Literacy Movement Intervention on the reading skills of fifth grade students at SDN Menanggal 601 Surabaya. According to Hidayati and Putra (2021), pre-learning literacy plays an important role in the transition to the world of formal literacy at school. Prasetyo (2021) explains reading skills as the ability to absorb information from text, which is an interactive process to understand the meaning and message contained. This research was motivated by problems regarding the implementation of the Pre-Learning Literacy Movement Intervention program for fifth grade students at SDN Menanggal 601 Surabaya which were still relatively weak, some students did not read but only looked at the pictures in the books. This research uses a causal quantitative method using an ex post vacto research design. The population used in this research was all Class V students at SDN Menanggal 601 Surabaya, totaling 60 students. The sample used was 30 students from class VB as the experimental class, and 30 students from class VA as the actual class used for the research. Data collection techniques use questionnaires, tests, interviews and documentation. Instrument testing uses validity and reliability. Prerequisite tests use the normality test and homogeneity test. Test the hypothesis in the form of a Paired Sample T-Test t test. To find out the value of the ttable distribution, it is seen based on df = 29 with a level of a = 0.05. Because the value of tcount > ttable (35,652 > 1,699) and Sig (2-tailed) 0.01 < 0.05, Ho and Ha are accepted.